2021
DOI: 10.1002/anie.202014706
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Urease, a Ni‐Enzyme: The Reactivity of a Key Thiol With Mono‐ and Di‐Substituted Catechols Elucidated by Kinetic, Structural, and Theoretical Studies

Abstract: The inhibition of urease from Sporosarcina pasteurii (SPU) and Canavalia ensiformis (jack bean, JBU) by a class of six aromatic poly‐hydroxylated molecules, namely mono‐ and dimethyl‐substituted catechols, was investigated on the basis of the inhibitory efficiency of the catechol scaffold. The aim was to probe the key step of a mechanism proposed for the inhibition of SPU by catechol, namely the sulfanyl radical attack on the aromatic ring, as well as to obtain critical information on the effect of substituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 49 publications
4
19
0
Order By: Relevance
“…In this equation, the k 1 and k 2 constants are functions of the single kinetic constants that regulate each step of the inactivation mechanism as well as the concentration of the inhibitor (Scheme 1). In order to quantitatively compare the inhibition strengths of HQ, MHQ, and t BHQ, the values of the k 1 ⋅ k 2 products determined for the data collected at a single and shared inhibitor concentration (1.6 mM) are reported in Table 5, as already done for catechol and its mono‐ and di‐methyl derivatives [26,27] . The resulting analysis showed that the inactivation proficiency of the hydroquinone derivatives follows the order HQ≃MHQ> t BHQ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this equation, the k 1 and k 2 constants are functions of the single kinetic constants that regulate each step of the inactivation mechanism as well as the concentration of the inhibitor (Scheme 1). In order to quantitatively compare the inhibition strengths of HQ, MHQ, and t BHQ, the values of the k 1 ⋅ k 2 products determined for the data collected at a single and shared inhibitor concentration (1.6 mM) are reported in Table 5, as already done for catechol and its mono‐ and di‐methyl derivatives [26,27] . The resulting analysis showed that the inactivation proficiency of the hydroquinone derivatives follows the order HQ≃MHQ> t BHQ.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic measurements : Pre‐incubation experiments were conducted at 25 °C as previously described [24,26,27] . In brief, a solution of 50 μg mL −1 active JBU dissolved in 20 mM HEPES buffer, pH 7.5, was 100‐fold diluted in Cresol Red (CR) buffer, consisting of 30 mg L −1 CR dissolved in 2 mM HEPES buffer (pH 7.5), 2 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can either directly bind to the nickel ions in the urease active site or modify specific cysteine residue located on the mobile flap covering the dinickel center of the enzyme (Svane et al 2020;Mazzei et al 2020). The flap is essential for urease activity as it controls substrate access to the active site (Mazzei et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the proposed 2-MA inhibitor contains a thiol moiety, which is known to display active inhibition of the urease enzyme, as described elsewhere 23 , 24 . Urease inhibitors have been extensively examined by previous researchers as described by 25 , 26 . However, many focus on their use in agriculture and few test their use on medicinally relevant bacterial ureases such as those from P. mirabilis .…”
Section: Introductionmentioning
confidence: 99%